Data Integration and Data Engineering Techniques (International Journal of Scientific Research and Management (IJSRM), 2024)
Data integration and data engineering techniques play a crucial role in the modern data landscape, facilitating the seamless amalgamation of diverse data sources to derive meaningful insights. As organizations increasingly rely on big data analytics, the need for efficient and robust data integration methodologies becomes paramount. This paper explores various techniques for data integration, including Extract, Transform, Load (ETL), data virtualization, and data federation, emphasizing their applicability across different domains. Additionally, we discuss data engineering practices that ensure the quality, scalability, and accessibility of integrated data, such as data modeling, pipeline architecture, and real-time data processing. By examining case studies and emerging trends, this work highlights the significance of these techniques in enabling organizations to harness the full potential of their data, ultimately driving informed decision-making and fostering innovation in an increasingly data-driven world.